Peran Kebijakan Pemerintah Dalam Memoderasi Pengaruh Strategi Bisnis Terhadap Kinerja Usaha - Suriyanti, Linda Hetri; Binangkit, Intan Diane (Jurnal Akuntansi dan Ekonomika, 2019)
This study aims to determine the effect of business strategies on business performance and the influence of business strategies on business performance through government policies. The sample in this study was food and beverages MSMEs in Pekanbaru. In this study,data was collected in two ways (library research and field research). This study used Moderated Regression Analysis (MRA). Based on the results of the test, it was concluded that business strategies influences government policy. This result shows that business strategies can determine the level of business performance. A business that has a business strategy that is directed precisely and effectively will produce good performance for the business. In addition, the results of the study also concluded that business strategies did not affect business performance through government policies. This is because most businesses that are run are continuing from their parents' business, so that they have a fixed market share and customers. So that government policies do not mediate the influence of business strategies on company performance.